Design and development of a rice hull-biomass cookstove. - Paita, Bernabe L.
Biofuels from biomass abound from agricultural produce and waste, and from forestry products and aquatic plants. Rice hull from rice biomass is a milling by product which can be used as fuel for a variety of purposes including household cooking. Similarly, coconut shell and husk are by products and are used as biofuels. Previous studies on rice hull stoves were reviewed. A set of criteria was generated in order to incorporate desirable features for the new rice hull biomass stove design. Work to improve existing rice hull stoves focused on minimizing attention required to maintain an effective flame, which is normally done by disturbing the fuel bed. The implementation of the combined center-tube, conical grate, and nozzle stove principles led to the development of a novel rice hull-biomass cookstove capable of using a variety of biofuels such as sawdust, wood chips, coconut shells and husk. Tests were conducted to evaluate the rice hull-biomass stove and the conical grate rice hull stove. Heat utilization efficiency of up to 20 percent translates to more fuel available for cooking.
Keywords: Rice hull-biomass cookstove; Biofuels